Daya Antibakteri Sari Buah Majapahit (Crescentia cujete L.) terhadap Bakteri Aeromonas salmonicida Secara In Vitro [Antibacterial Activity of The Juice Majapahit Fruit (Crescentia cujete L.) To Bacteria Aeromonas salmonicida Against In Vitro] - Boedi Setya Rahardja; Fitria Yusmita Sari; Yudi Cahyoko (Faculty of Fisheries and Marine Universitas Airlangga, 2011)
Abstract Bacteria are single-celled organisms, reproduce by dividing themselves (asexual) that reproduce by way of extending the cell nucleus followed by cell division called binary fission (Prajitno, 2005) and can only be viewed with a microscope because of their small size (Dwijoseputro, 1989 .) One of the bacteria that cause the greatest failures in the cultivation of freshwater fish and sea water is furunculosis (presence of a number of furuncles at the same time) caused by the bacterium Aeromonas salmonicida (Cipriano and Bullock, 2001). A. salmonicida is divided into several subspecies, among others, A. salmonicida subspecies salmonicida, subspecies masoucida, subspecies achromogenes and subspecies smithia (Hiney and Olivier, 1999). Fish infected with these bacteria will show symptoms such as fish body color becomes darker, the ability to swim down, resulting haemorrhagic septicemia, the abdomen looks bloated, the eyes and slightly protruding damaged fish (exopthalmia), all damaged fins, and gills become pale and damaged (Buller, 2004). The method used in the research is experimental method. This study aims to determine whether fruit majapahit juice (C. cujete L.) has antibacterial power against bacteria A. salmonicida and find out whether or not sensitive majapahit juice (C. cujete L.) in inhibiting the growth of bacteria A. salmonicida with standard comparator antibiotic kanamycin. Research conducted at the Laboratory of Bacteriology Hall Fish Quarantine Airport Highway Ir. H. Juanda Street No.23, Semambung Village Sedati- Sidoarjo District, East Java Province in February 2011. The results showed that the juice majapahit (C. cujete L.) could inhibit bacterial growth of A. salmonicida against in vitro, but when compared with standard antibiotic kanamycin 30 µg still relatively insensitive to inhibit bacterial growth of A. salmonicida.